HUBUNGAN PANJANG-BOBOT, FAKTOR KONDISI DAN KARAKTERISTIK BIOMETRIK IKAN LELE AFRIKA (Clarias gariepinus) ALBINO ASAL THAILAND - Bambang Iswanto; Rommy Suprapto; Pudji Suwargono (Research Center for Biology-Indonesian Institute of Sciences, 2020)
The African catfish (Clarias gariepinus) has been introduced several times to Indonesia, including from Thailand (Paiton strain). The breeding of Paiton strain resulted in albino individuals. The present study aimed to investigate the length-weight relationship, condition factor and biometric characteristic of those albinos. Five pairs of each albino and normal coloured Paiton African catfish were artificially bred. Larvae and juveniles from each pair were reared one month of larval rearing phase, one month of nursery phase and two months of grow-out phase, then the total length and body weight were measured for length-weight relationship and condition factor analysis, finally the biometric was characterized. The present study revealed that the relationship between total length (L) and body weight (W) of the Paiton African catfish was positive allometric (W = 0.0038L3.23 in the albino and W = 0.0027L3.27 in the normal coloured one). The albino Paiton African catfish was more rotund (condition factor of 0.79±0.07) than the normal colored one (condition factor of 0.68±0.06). Biometrically, the albino Paiton African catfish has a bigger head portion and fewer dorsal and anal fin rays than those of the normal coloured one. Despite the colour difference, the albino and normal coloured Paiton African catfish were morphologically different.